I-PASS Training Significantly Improves Nurses’ Handoff and Information Exchange Quality in Hospital Settings - Dewi Allo; Sella Dwi Astia Ningrum; Evra Yusandra Arifin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Patient safety culture encompasses shared values, beliefs, and norms regarding the importance of safety in healthcare settings. Ineffective communication during handoffs and information exchange can lead to medical errors, complications, and even an increased risk of mortality. This study aimed to analyze the effectiveness of I-PASS training on the quality of handoffs and information exchange among nurses at Hospital X, West Jakarta. This study employed a quantitative approach with a pre-experimental design and was conducted from February to March 2026. The sample consisted of 56 nurses who met the inclusion criteria: working in inpatient wards, ICU, and emergency departments; willing to participate; levels PK 2 and 3; and actively involved in handoffs and information exchange processes. The data collection tool was a questionnaire. The results showed that the majority were aged 26–35 years (66.1%), female (75%), PK level 2 (85.7%), and D3 Nursing (60.7%). The results of the I-PASS training for nurses after training showed that the majority (80.4%) had good results, and the quality of handoffs and information exchange after training was good (57.1%). There was a relationship between age (p-value = 0.032) on the quality of handoffs and information exchange. There was a significant difference in the quality of handoffs and information exchange before and after the intervention (p-value = 0.000). The results of the multivariate analysis showed that age (p-value = 0.019) and I-PASS training (p-value = 0.029) significantly influenced the quality of handoffs and information exchange (p < 0.05). The coefficient of deter mination (R²) was 0.112, indicating that these two factors contributed 11.2% to explaining the quality of handoffs and information exchange. Hospitals are recommended to establish I-PASS training as a structured and sustaiable nursing development program by integrating I-PASS-based learning mechanisms into standard operating procedures (SPOs), ensuring consistent implementation among all nursesKeywords: I-PASS training; quality of handoffs and information exchange; nurses